Content and distribution of mercury in coal and its relation to depositional environment—A case study on coals from the Shanxi Formation in Huainan Coalfield - Zheng, Liugen; Zhang, Liqun; Wang, Yunlong; Chen, Yeyu; Chen, Yongchun; An, Shikai; Xu, Yanfei (Frontiers in Earth Science, 2023)
Mercury in coals might emit into the environment from coal combination, and finally cause environmental pollution. In this paper, 26 coal samples were selected from No. 1 which is coal in the Shanxi Formation of Zhangji and Xinjier mines in the Huainan coalfield. The mineralogical and geochemical components of coal samples were determined by DMA-80 mercury-measuring instrument, XRF, XRD, ICP-MS, and the relationship between the depositional environment of the coal seam and mercury enrichment was analyzed. The results show that the mercury content of coal in the study area ranged from 0.03 to 0.93 μg/g, with an arithmetic means of 0.21 μg/g, higher than the background values of coal in China and the world. The mercury content of Shanxi Formation coal varied among different mines, the arithmetic mean value of mercury in Zhangji coal mine and Xinjier mine coal is 0.35 μg/g and 0.12 μg/g respectively. Due to the complex depositional environment and depositional facies, the distribution of mercury content in the coal seam is quite different. XRD, Microscopic observation and the ratio of (CaO + MgO + Fe2O3)/(SiO2+ Al2O3) and Al2O3/TiO2 show that the main mineral in the depositional environment of this study area is kaolinite, quartz and pyrite, and the depositional facies are intercontinental and sea-land, so the parent rock type belongs to acid bedrock. The Ni/Co, Sr/Ba and Sr/Cu ratios were used to indicate a weak oxidation-reduction, Marine salt water, and an arid and hot environment. The vertical distribution of mercury in coal and the characteristics of the depositional environment are combined to show that mercury in coal is easily affected by redox conditions, paleosalinity and paleoclimate in the depositional environment. At the same time, mercury accumulation is more easily in the depositional environment dominated by seawater intrusion than in the terrigenous input.